A Study on the Expected Quality of Students and Academic Administration of Roi Et Demonstration School in Kohkaew Sub–district, Selaphum District, Roi Et Province - อุดมสันต์, นิธินาถ; พิมขาลี, ณัฐวุฒิ; ประชามิ่ง, สุจิตรา; พิมพ์พรม, ธนกฤษ (Journal of Roi Et Rajabhat University, 2016)
The objective of this research was to study the parents' expectation on the quality of students and academic administration at Roi Et Demonstration schools. The sample consisted of parents at Roi Et Demonstration School in the Kohkaew Subdistrict of Selaphum District in Roi Et Province. The total number of participants was 142 parents using the Purposive Sampling Method (PSM). The instrument was a questionnaire, which was described in terms of the mean, percentage and standard deviation (S.D.). The results of the study were as follows. The parent’s expectation on the quality of students and academic administration at the Roi Et Demonstration School was overall at a high level. The specific areas examined were arts, music, sports, good health habits, physical health, good mental health and being drug–free (happiness). Most parental expectations were at the high level, especially in the area of living drug–free, free from bad influences. The pursuit of benefits was at the highest level followed by the development of the curriculum also at the high level. In this area, parents expect the administration to support an enabling environment to learn at the highest level. Basic knowledge and skills based on the curriculum and learning personal skills as well as love of working (smart) were minimal at a high level. In the area of creativity and imagination was at a high level.